Women’s Empowerment Through Bouquet Craft Training in Rural Communities - Mochamad Junaidi; Ilmi Usrotin Choiriyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Women’s economic empowerment is a strategic pathway to strengthening household welfare and community resilience in rural areas. Specific Background: In Kendalpecabean Village, limited income opportunities for women encouraged the village government to initiate bouquet craft training as a community-based economic activity. Knowledge Gap: Previous studies rarely explain how empowerment processes operate through concrete dimensions at the village level. Aims: This study analyzes women’s empowerment in improving the local economy through bouquet craft training. Results: Using a qualitative descriptive approach, the findings show that empowerment was realized through four dimensions: enabling, facilitating, consulting, and collaborating, involving village officials, PKK members, and external partners. The program increased skills, confidence, and income opportunities, although limited training frequency constrained broader participation. Novelty: This study offers an integrated analysis of empowerment dimensions applied to a creative craft-based village program. Implications: The findings suggest that sustainable empowerment requires continuous training, mentoring, and stronger market access to bridge gaps between skills acquisition and economic practice.